1973
DOI: 10.1037/h0034978
|View full text |Cite
|
Sign up to set email alerts
|

Name stereotypes and teachers' expectations.

Abstract: Acknowledging effects of implicit biases in teachers' expectations upon the educational process, it was conjectured that teachers' evaluations of children's performance may be systematically associated with stereotyped perceptions of first names. Short essays actually written by fifth-grade students were presented for evaluation to teachers and college sophomores. Authorship of the essays was randomly linked with boys and girls with common, popular, and attractive names, as well as with rare, unpopular, and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
1
3

Year Published

1975
1975
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(59 citation statements)
references
References 9 publications
0
55
1
3
Order By: Relevance
“…Parents’ projected expectations may be internalized by their offspring and crystallize into his or her evolving psychological matrix through different developmental processes [18]. The chosen name may have both a positive [19] and negative impact on the psychological development of the child. For example, androgynous names that were attributed to gender confusion of the parents may affect the offspring as well [20].…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ projected expectations may be internalized by their offspring and crystallize into his or her evolving psychological matrix through different developmental processes [18]. The chosen name may have both a positive [19] and negative impact on the psychological development of the child. For example, androgynous names that were attributed to gender confusion of the parents may affect the offspring as well [20].…”
Section: Discussionmentioning
confidence: 99%
“…With the re-emergence of interest in women's status in the 1960's came reassessment of social institutions and customs relating to women, including that of surname change at marriage. Reviews of developments in the women's rights movement are available (Freeman, 1975;Kanowitz, 1969) and include some information on married women's rights to determine their own names.…”
Section: Fall 1981mentioning
confidence: 99%
“…Several studies (Harari & McDavid, 1973;Levine & Willis, 1994;McDavid & Harari, 1966;Savage & Wells, 1948) have concluded that people with unpopular first names are perceived by themselves and by others as inferior to people with popular names. If health is related to self-esteem (McGee & Williams, 2000;Trzesniewsky et al, 2006), then life expectancy may be lower for people with unusual first names.…”
mentioning
confidence: 98%